2022
DOI: 10.1155/2022/2930310
|View full text |Cite
|
Sign up to set email alerts
|

Methylation Pattern Mediated by m6A Regulator and Tumor Microenvironment Invasion in Lung Adenocarcinoma

Abstract: Background. Recent research has established the existence of epigenetic modulation of the immune response. The possible involvement of RNA-n6-methyladenosine (m6A) alteration in tumor microenvironment (TME) cell invasion, on the other hand, is unknown. Methods. Based on 23 m6A regulators, we examined the alteration patterns of m6A in 629 LUAD tissues and comprehensively connected these modification patterns with TME cell invasion characteristics. The m6A score was calculated, and the m6A modification pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
(42 reference statements)
0
31
0
Order By: Relevance
“…Studies have showed that phytochemicals from natural products induce the accumulation of ROS by damaging DNA biomolecules and triggering cell death-related signaling pathways, including m6A modification [ 34 ]. m6A alteration is critical in the creation of tumor immune microenvironment variety and complexity in lung cancer [ 35 ]. Reactive oxygen species (ROS) can damage lipids, nucleic acids, and proteins, thereby altering their functions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have showed that phytochemicals from natural products induce the accumulation of ROS by damaging DNA biomolecules and triggering cell death-related signaling pathways, including m6A modification [ 34 ]. m6A alteration is critical in the creation of tumor immune microenvironment variety and complexity in lung cancer [ 35 ]. Reactive oxygen species (ROS) can damage lipids, nucleic acids, and proteins, thereby altering their functions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that bioinformatics has amazing prospects in dealing with genomic variation, TME, and precision therapy (Jiang et al, 2020;Wang et al, 2021;Jiang et al, 2022;Yu et al, 2022). As previous results strongly suggested higher sensitivity to treatment among patients in the low-risk group, we finally analyzed the sensitivity of COAD patients in both groups towards chemotherapy and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The following are the criteria we use to choose datasets: first, the sample size must be larger than 100; second, the data set must include both a treatment and a healthy control; third, in both the patient and control groups, there must be at least 10 cases in each. These regulators consisted of nine writers (METTL3, METTL14, METTL16, WTAP, VIRMA, RBM15, RBM15B, CBLL1, and ZC3H13), two erasers (FTO and ALKBH5), and 15 readers (YTHDC1, YTHDC2, YTHDF1, YTHDF2, YTHDF3, HNRNPC, FMR1, LRPPRC, HNRNPA2B1, IGFBP1, IGFBP2, IGFBP3, RBMX, ELAVL1, and IGF2BP1) ( Dai et al, 2021 ; Jiang et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%